Cardiovascular Intervention and Therapeutics - Kobayashi, Yoshio; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer.)
Cardiovascular Intervention and Therapeutics (CVIT) is an international journal covering the field of cardiovascular disease and includes cardiac (coronary and noncoronary) and peripheral interventions and therapeutics. Articles are subject to peer review and complete editorial evaluation prior to any decision regarding acceptability. CVIT is an official journal of The Japanese Association of Cardiovascular Intervention and Therapeutics.
Keywords: Interventional radiology; Cardiology; Cardiology; Interventional Radiology